Assessing the sustainability of different poultry production systems: A multicriteria approach. (20th February 2019) - Rocchi, L.; Paolotti, L.; Rosati, A.; Boggia, A.; Castellini, C.
Abstract: The aim of this study was to assess the sustainability of three different poultry production systems, in order to evaluate their suitability to address human food need, as well as their environmental sustainability, economic feasibility and animal welfare. The three systems compared were: a conventional intensive indoor system, a free range system and a free range system combined with an olive orchard (where chickens grazed in an orchard instead of in an area used solely for the grazing). A model based on multicriteria decision analysis was developed, using environmental, social and economic criteria. Environmental criteria were estimated using a life cycle assessment, while economic and social criteria were both collected on farms and from the literature. The analysis considered the preferences of different stakeholders involved in the production i.e. farmers, consumers, and scientists. The combined system ranked at the top position according to all three groups of stakeholders, followed by the free range and then the intensive systems. The stability of results was verified by performing a sensitivity analysis, in particular a weight stability analysis. The results showed that the final ranking was quite stable, as only four out of the 20 criteria considered had rank reversal (i.e. the ability to change the relative positions of two cases in a ranking). For these four criteria (i.e. Mortality Rate, Feed Conversion, Fossil Fuels and Land Use), rank reversal was easier between the free-range and the intensive systems, than between the combined and the intensive systems. Highlights: Sustainability of three poultry systems was compared with a multicriteria approach. Three groups of stakeholders (farmers, consumers, scientists) were involved. Rearing free range chickens in an olive orchard was preferred by all stakeholders. A sensitivity analysis indicated that results were stable.